Programming Evolution through Computational Thinking Using The Bibliometrics Analysis - Mohd Rosli, Nurbaya; Mohd Matore, Mohd Effendi Ewan; Husnin, Hazrati (PT Mattawang Mediatama Solution, 2025)
The increasing significance of programming in various fields has made understanding its evolution a crucial academic pursuit. Despite the growing importance of programming, there is a lack of comprehensive analysis that integrates programming evolution with the nuances of computational thinking. This study explores an in-depth examination of the developmental trajectory of programming, contextualized within the broader framework of computational thinking. The aim of the paper is to decode the patterns, trends, and shifts in programming paradigms, tools, and education, contributing to the academic discourse on the subject. Using bibliometric analysis, the study examines a broad array of academic publications and data from the past decade. Advanced data mining in Scopus database and VOSviewer 1.6.20 are employed to trace the progression of programming concepts and their educational implications. Findings indicate a major transition from traditional paradigms to more inclusive, intuitive approaches that emphasize real-world problem-solving and interdisciplinary applications. The analysis reveals a significant shift from traditional programming paradigms towards more inclusive and intuitive approaches, emphasizing real-world problem-solving and interdisciplinary applications. While, educational trends show a gradual integration of computational thinking into curricula, reflecting the need to equip learners with relevant programming skills.